65.0k views
5 votes
How do I do this please help

How do I do this please help-example-1
User Ghlouw
by
4.5k points

2 Answers

4 votes

Answer:

C) 4,0

Explanation:

Basically to find zeros you set up the expression equal to zero.

First pair is (0,0) they derived this by setting the leftmost x to 0 so x=0, this meant that when x was plugged back into the equation y = x(x-4) the y value we got out was 0 because y = 0 (0-4) = 0, thus the pair (0,0).

For second pair, we set up x-4= 0, solve this to get x = 4 (add 4 to both sides). Now plug this back into full equation y= 4 (4-4)= 0, you get y=0 and your ordered pair is (4,0) which is the second pair of zero.

Zero are x-intercept where y is zero which is the main reason why we setup x=0 or x-4=0 to start with.

User Aniruddha
by
4.8k points
5 votes

Hi there!

»»————- ★ ————-««

I believe your answer is:

[answer]

»»————- ★ ————-««

Here’s why:

  • According to the question, the factored form of the given quadradic expression is:
    x(x-4).
  • I have graphed this on a graphing program.

⸻⸻⸻⸻

  • When graphed, the parabola passes the points (0,0) and (4,0). They are the zeros.

⸻⸻⸻⸻

  • Option C (4,0) would be the other 'zero'.

⸻⸻⸻⸻

See graph attached.

»»————- ★ ————-««

Hope this helps you. I apologize if it’s incorrect.

How do I do this please help-example-1
User Ramakrishna Joshi
by
5.5k points